The Islamic Education for Single Parent's Family: A Case study in Karaban Jaya - Ubabuddin Ubabuddin; Triyo Supriyatno; Nuraini Nuraini (AT-TA'LIM, 2020)
Everyone craves having family integrity. Because the integrity of the family makes it easy to share roles between fathers and mothers both in earning a living or doing household chores including the obligation to educate their children. But in reality, many find all these roles to be borne by one person or called a single parent, could be a father or mother. Usually it happens because of separation due to divorce or death of one of them, thus making the responsibility of raising all their children more difficult. For children, family (both parents) is the main environment they need. So from that family the parents can provide better protection and education for their future life provisions. The obligation of parents as mentioned in the Qur'an is to protect themselves and their families from the fires of hell. Then the family should become a madrasa in introducing Islamic education. As an educator in the family, parents must have the expertise and art of educating, one of the skills that must be mastered is the method. There are several methods that families can use in educating their children. This research focuses: how is the pattern of single parent care in the perspective of Islamic education to children in Karaban Jaya . The research method is qualitative with a case study approach. The results showed that parenting to educate children in single parent families in Keraban Jaya Village was by example, giving advice, motivation, and giving attention and supervision to children from young to teenagers. While the values of Islamic education taught include strengthening monotheism, worship, moral or moral cultivation, forming mentality and applying discipline or control.